Investment in Learning English as an Additional Language: A Study with Pre-service Teachers - Ortega Prieto, Pedro Felipe; Hernandez Vargas, Maria Angelica; Kaya, Jean; Olaya Leon, Alba (Colombian Applied Linguistics Journal, 2024)
Learning additional languages is an experience and a process influenced by numerous aspects. This article presents a qualitative case study focused on the aspects influencing the investment of seven learners of English as an additional language, all of whom are pre-service teachers pursuing bachelor’s degrees in English education. The data under consideration is part of a larger intervention-based action research study that explored the language learning experiences of twenty pre-service teachers enrolled in a teacher preparation program at a public university in Colombia. The study is grounded in Darvin and Norton’s (2015) concept of investment and highlights the significance of communities of practice (Wenger, 2011). We analyzed open-ended interviews using Saldaña’s (2016) coding framework. The findings suggested that the investment of additional language learners can be influenced by their teachers’ pedagogical practices, the learning communities created by teachers, and the learners’ own imagined selves or identities. We discussed the implications of these findings for language teachers, language centers or institutes, and teacher education programs.